2009
DOI: 10.1016/j.neuron.2009.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Cation-Chloride Cotransporters and Neuronal Function

Abstract: Recent years have witnessed a steep increase in studies on the diverse roles of neuronal cation-chloride cotransporters (CCCs). The versatility of CCC gene transcription, posttranslational modification, and trafficking are on par with what is known about ion channels. The cell-specific and subcellular expression patterns of different CCC isoforms have a key role in modifying a neuron's electrophysiological phenotype during development, synaptic plasticity, and disease. While having a major role in controlling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
782
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 715 publications
(811 citation statements)
references
References 236 publications
16
782
0
1
Order By: Relevance
“…The driving force for the Cl − current that is necessary for hyperpolarizing IPSPs is generated by the K + -Cl − cotransporter KCC2, a neuron-specific cotransporter that extrudes Cl − under physiological conditions in adulthood (Farrant and Kaila, 2007;Blaesse et al, 2009). Accordingly, the change in GABA A receptor-mediated responses from depolarizing to hyperpolarizing seen during early neuronal development is coupled to the induction of the KCC2 expression (Rivera et al, 1999); these data thus support the view that KCC2 is the main Cl − extruder to promote fast hyperpolarizing postsynaptic inhibition in the brain.…”
Section: Gaba a Receptor-mediated Phasic Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The driving force for the Cl − current that is necessary for hyperpolarizing IPSPs is generated by the K + -Cl − cotransporter KCC2, a neuron-specific cotransporter that extrudes Cl − under physiological conditions in adulthood (Farrant and Kaila, 2007;Blaesse et al, 2009). Accordingly, the change in GABA A receptor-mediated responses from depolarizing to hyperpolarizing seen during early neuronal development is coupled to the induction of the KCC2 expression (Rivera et al, 1999); these data thus support the view that KCC2 is the main Cl − extruder to promote fast hyperpolarizing postsynaptic inhibition in the brain.…”
Section: Gaba a Receptor-mediated Phasic Inhibitionmentioning
confidence: 99%
“…This view is supported by experimental evidence in which it was shown that following damage to afferents in the spinal cord, BDNF liberated by microglia activates trkB receptors leading to a KCC2 down-regulation and a depolarizing shift in GABAergic reversal potentials associated with pathological pain responses (Price et al, 2005;Lu et al, 2008). It has also been shown that experimentally induced interictal activity in hippocampal slices maintained in vitro, downregulates KCC2 mRNA and protein expression in CA1 pyramidal neurons, which leads to a reduced capacity for neuronal Cl − extrusion (Rivera et al, 2002(Rivera et al, , 2004Blaesse et al, 2009). Alterations in the balance of NKCC1 and KCC2 activity have also been identified in the subiculum and hippocampus of epileptic patients by Munoz et al (2007).…”
Section: Gaba a Receptor-mediated Inhibition May Implement Epileptifomentioning
confidence: 99%
“…The action of GABA depends on the concentration of intracellular Cl − ([Cl − ] i ): when the [Cl − ] i is high during embryonic development, GABA A R activation results in Cl − efflux, membrane depolarization, and excitatory synaptic transmission; whereas low [Cl − ] i results in Cl − influx, membrane hyperpolarization, and thus inhibitory synaptic transmission (1)(2)(3). The low [Cl − ] i that makes fast GABA A Rmediated synaptic inhibition possible is maintained by the neuronspecific K + -Cl − cotransporter KCC2 (4), a member of the cationchloride cotransporter SLC12 gene family (5). KCC2 is essential for survival, as KCC2 knockout mice die immediately at birth due to respiratory failure (6).…”
mentioning
confidence: 99%
“…KCC2 is essential for survival, as KCC2 knockout mice die immediately at birth due to respiratory failure (6). In the adult nervous system, decreased KCC2 expression correlates with neuropathic pain, spasticity following spinal cord injury, and epileptic seizures (5,(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…The temporal expression of KCC2 is regulated by a number of factors, including neuronal activity, GABA level, and brain-derived neurotrophic factor (Aguado et al, 2003;Fiumelli and Woodin, 2007;Ganguly et al, 2001). Moreover, the activity of NKCC1 and KCC2 has been shown to be regulated by various mechanisms, including phosphorylation, cell volume, and oligomerization of KCC2 (Blaesse et al, 2009;Payne et al, 2003).…”
Section: Introductionmentioning
confidence: 99%